The role of university-based induction in beginning elementary teacher enactment of effective mathematics teaching. Issue 3 (27th May 2018) - Schwartz, Catherine Stein; Ticknor, Anne Swenson
Abstract: The purpose of this paper is to describe the school-based contextual constraints perceived by beginning elementary teachers as they attempted to enact their visions of effective mathematics teaching and the components of a mathematics-specific, university-based induction program designed to support elementary teachers in their teaching of mathematics. A significant number of beginning teachers in the program indicated that curriculum pacing guides and grade level teachers often discouraged their enactment of effective mathematics teaching. We describe the components of the induction program in general and then discuss the specific ways that program mentors, who were elementary teachers with expertise in mathematics teaching, supported beginning teachers in navigating the constraints identified. Data suggest that supporting teachers' pedagogical agency to navigate local school contexts should be an additional consideration in teacher preparation and induction programs.